Analysis of the Listening Ability of PGSD Students in Online Learning - Elfira Mahmud; Pratiwi Pujiastuti; M. Fakhrur Saifudin (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze students’ listening skills in online learning in language skills courses. In addition, this study also aims to find factors that affect students’ listening difficulties. This study was designed using descriptive research with a quantitative and qualitative approach involving 86 students taking a listening skill test. The results showed that the students had very good listening skills, as indicated by the scores of listening skills, most of the students were in the 82,5-95 range. However, the result is still only on the ability to listen in simple texts, so that listening skills need to be improved again to understand more complex information. Factors that affect listening difficulties are internal factors, that is mental readiness in understanding the information being listened to, and external factors such as inadequate places and poor internet networks.